Stable power supply of an independent power source for a remote island using a Hybrid Energy Storage System composed of electric and hydrogen energy storage systems. (5th April 2022) - Fukaume, S.; Nagasaki, Y.; Tsuda, M.
Abstract: We propose a self-sustaining power supply system consisting of a "Hybrid Energy Storage System (HESS)" and renewable energy sources to ensure a stable supply of high-quality power in remote islands. The configuration of the self-sustaining power supply system that can utilize renewable energy sources effectively on remote islands where the installation area is limited is investigated. It is found that it is important to select renewable energy sources whose output power curve is close to the load curve to improve the efficiency of the system. The operation methods that can increase the cost-effectiveness of the self-sustaining power supply system are also investigated. It is clarified that it is important for increasing the cost effectiveness of the self-sustaining power supply system to operate the HESS with a smaller capacity of its components by setting upper limits on the output power of the renewable energy sources and cutting the infrequent generated power. Highlights: Self-sustaining power supply system with renewable energy source and HESS is proposed. Proposed power system enables stable supply of high-quality power to remote islands. Selecting renewable energy source according to power consumption trend is important. We get optimal ratios of capacity and output suppression of renewable energy sources. These optimal ratios are important for efficient and stable long-term power supply.